Atypical Form of Cervicofacial Actinomycosis Involving the Skull Base and Temporal Bone. (February 2019) - McCann, Adam; Alvi, Sameer A.; Newman, Jessica; Kakarala, Kiran; Staecker, Hinrich; Chiu, Alexander; Villwock, Jennifer A.
Background: Cervicofacial actinomycosis is an uncommon indolent infection caused by Actinomyces spp that typically affects individuals with innate or adaptive immunodeficiencies. Soft tissues of the face and neck are most commonly involved. Actinomyces osteomyelitis is uncommon; involvement of the skull base and temporal bone is exceedingly rare. The authors present a unique case of refractory cervicofacial actinomycosis with development of skull base and temporal bone osteomyelitis in an otherwise healthy individual. Methods: Case report with literature review. Results: A 69-year-old man presented with a soft tissue infection, culture positive for Actinomyces, over the right maxilla. Previous unsuccessful treatment included local debridement and 6 weeks of intravenous ceftriaxone. He was subsequently treated with conservative debridement and a prolonged course of intravenous followed by oral antibiotic. However, he eventually required multiple procedures, including maxillectomy, pterygopalatine fossa debridement, and a radical mastoidectomy to clear his disease. Postoperatively he was gradually transitioned off intravenous antibiotics. Conclusions: Cervicofacial actinomycosis involves soft tissue surrounding the facial skeleton and oral cavity and is typically associated with a history of mucosal trauma, surgery, or immunodeficiency. The patient was appropriately treated but experienced disease progression and escalation of therapy. Although actinomycosis is typically not an aggressive bacterial infection, this case illustrates the need for prompt recognition of persistent disease and earlier surgical intervention in cases of recalcitrant cervicofacial actinomycosis. Chronic actinomycosis has the potential for significant morbidity.